2020
DOI: 10.28991/scimedj-2020-0203-7
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the Editor: Prevention of Depression and Psychological Stress by Studying Book in Quarantine Conditions of COVID-19

Abstract: With the occurrence pandemic of Coronavirus disease (COVID-19), the World Health Organization and health officials in all countries of the world were forced to comply with quarantine conditions. On the one hand, the stress of this dangerous viral disease, and other hand, staying home for an indefinite period of time does not have pleasant consequences. The announcement of an increase in the number of patients with the disease and the death toll also adds to the emotional excitement. Therefore, to prevent menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…The relationship between stress, depression, and anxiety supports compensatory and protective models of resilience. This is also consistent with the results of previous resilience model studies that the higher score of resilience, better able to resist the negative effect of stress, and the more positive the psychological health [ 6 , 28 , 51 ]. However, in the study of resilience in adolescents, resilience only regulating the relationship between stress and depression not between stress and anxiety [ 32 ].…”
Section: Discussion and Limitationssupporting
confidence: 92%
“…The relationship between stress, depression, and anxiety supports compensatory and protective models of resilience. This is also consistent with the results of previous resilience model studies that the higher score of resilience, better able to resist the negative effect of stress, and the more positive the psychological health [ 6 , 28 , 51 ]. However, in the study of resilience in adolescents, resilience only regulating the relationship between stress and depression not between stress and anxiety [ 32 ].…”
Section: Discussion and Limitationssupporting
confidence: 92%
“…Therefore, to prevent mental and psychological diseases as well as other social harms, people can make it easier and more tolerable of quarantine conditions and issues on the margins of illness, by studying and reading books. Research has shown that studying, especially reading books plays an important role in preventing diseases such as depression and stress (Arab-Rahmatipour et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conticini et al ( 2020 ) have suggested considering population, social habits, and meteorological condition together with air pollution when analyzing COVID-19 spread and mortality rates. Moreover, Arab-rahmatipour et al ( 2020 ) conclude that COVID-19 impacts not only the public health but also the mental health. However, caution is recommended by Bontempi ( 2020a ) who has shown that there is no strong evidence that COVID-19 diffusion mechanism occurs through the air using PM 10 as a carrier even though PM 10 was shown to have a linear functional relationship with cardiovascular disease and non-accidental mortality rate in Spain (Ortiz et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%